Influence of the Addition of Ni‐Coated Carbon Nanotubes on the Mechanical Properties of Highly Porous Zirconia Cellular Structures. Issue 1 (16th September 2021) - Henriques, Bruno; Fabris, Douglas; Lopes, Elvira; Moreira, Anderson C.; Mantovani, Iara F.; Fernandes, Celso P.; Fredel, Márcio C.
Abstract : Herein, the effect of the addition of Ni‐coated carbon nanotubes (CNTs) on the microstructure, mechanical properties, and morphology of zirconia porous cellular structures is studied, aiming to increase their mechanical strength. Highly porous structures of monolithic zirconia (ZrO2 ) and zirconia reinforced with Ni‐doped CNTs (ZrO2  + CNT/Ni) are fabricated through the replica method. Scanning electron microscopy and micro‐computed tomography (microCT) analyses show that ZrO2 + CNT/Ni specimens present lower overall porosity (88.0%) than monolithic ZrO2 (93.8%), indicating improved sintering kinetics. Compressive tests for the ZrO2  + CNT/Ni samples result in a compressive strength of 0.82 ± 0.10 MPa, a threefold value of that of the monolithic sample (0.25 ± 0.07 MPa). The ZrO2  + CNT/Ni samples also present a higher elastic modulus (41.02 ± 4.94 MPa) than the ZrO2 ones (21.92 ± 5.40 MPa). Thus, the addition of Ni‐coated CNTs significantly improves the strength of highly porous zirconia cellular structures. Abstract : Herein, structural and mechanical properties of highly porous zirconia foams reinforced with Ni‐coated carbon nanotubes (CNTs/Ni) are investigated. Incorporation of CNTs/Ni substantially improves the mechanical strength and elastic modulus of zirconia foams and slightly decreases the porosity. Such improvement may have arisen from synergic beneficial effects of carbon and nickel on the zirconia microstructure.